Clinical trial of the effects of postbiotic supplementation on inflammation, oxidative stress, and clinical outcomes in patients with CVA - Akram Rahimi; Shaimaa A. Qaisar; Tofigh Janeh; Hassanali Karimpour; Mitra Darbandi; Jalal Moludi (Scientific Reports)
Abstract Background Cerebrovascular accidents (CVAs), or strokes, are major global health concerns associated with oxidative stress, inflammation, and gastrointestinal complications. This study aimed to explore the impact of postbiotic supplementation in CVA patients, specifically in terms of oxidative stress, inflammation, and clinical outcomes, as an alternative to probiotics with potential advantages. Method A prospective, single-center, randomized, controlled trial was conducted with 120 CVA patients in Iran. These patients were admitted to the ICU to assess the severity of their strokes. Patients were randomly assigned to receive either postbiotic supplementation (n = 60) or a placebo (n = 60). Various biomarkers related to oxidative stress, inflammation, and clinical outcomes were assessed. Data on demographic characteristics, nosocomial infections, and laboratory measurements were collected. Gut microbiota analysis was also performed on fecal samples. Results After the 7-day intervention, postbiotic supplementation resulted in significant improvements in inflammatory markers, oxidative stress, and a reduced incidence of pneumonia compared with those in the control group, with the postbiotic group demonstrating notable decreases in the serum IL-1β levels (-1.79; 95% CI: = -2.9 to -0.64, p = 0.002 ), MDA levels (-30.5; 95% CI: -54.8 to -6.1, p = 0.015), Hs-CRP levels (-0.67; 95% CI:-1.1 to -0.26 mg/dl, p = 0.001) and TAC levels (62.5; 95%CI: 34.1 to 90.9, p < 0.001) compared with those in the placebo group. However, no significant differences in other clinical outcomes, including the NIHSS score, NUTRIC score, and APACHE II score, or the gut microbiota profile, were observed between the two groups. Conclusion Postbiotic supplementation improved the levels of inflammatory factors and oxidative stress markers and reduced the risk of pneumonia in CVA patients. Trial registration This trial is registered in the Iranian Registry of Clinical Trials (registration code IRCT20180712040438N7), Registration date 06122022.